Fibrinolysis in trauma patients: wide variability demonstrated by the Lysis Timer. (17th February 2019) - Roullet, Stéphanie; Weinmann, Laurent; Labrouche, Sylvie; Gisbert-Mora, Chloé; Biais, Matthieu; Revel, Philippe; Freyburger, Geneviève
Abstract: Hyperfibrinolysis contributes to the pathophysiology of trauma-induced coagulopathy. At present, systematic administration of tranexamic acid (TXA) is recommended in all patients in the early phase of trauma. However, there is some debate regarding whether TXA is beneficial in all trauma patients. A rapid and accurate tool to diagnose hyperfibrinolysis may be useful for tailoring TXA treatment. We conducted a proof-of-concept study of consecutive adult trauma patients. A first blood sample was obtained at the time of pre-hospital care (T1). Patients received 1 g of TXA after T1. A second sample was obtained on arrival at the emergency unit (T2). We examined coagulation, fibrin and fibrinogen formation and degradation. Fibrinolysis was assessed by determining tissue plasminogen activator (t-PA) antigen and plasminogen activator inhibitor 1 (PAI-1) activity and global fibrinolysis capacity assay using a device developed by Hyphen BioMed: the Lysis Timer (GFC/LT). The study population consisted of 20 patients (42 ± 21 years, index of severity score 32 ± 21). Both coagulation and fibrinolysis were altered at T1. GFC/LT values exhibited hyperfibrinolysis only in five patients. Principal component analysis carried out at T1 showed two main axes of alteration. The major axis was related to coagulation, altered in all patients, while the second axis was related to fibrinolysis. GFC/LT was mainly influenced by PAI-1 activity while fibrin monomers were related to the severity of trauma. At T2, GFC/LT exhibited the marked effect of TXA on clot lysis time. In conclusion, GFC/LT demonstrated huge variation in the fibrinolytic response to trauma.